Observation of upstream particle movement without the involvement of the marangoni effect - Aryan Hussain Sahir; Saiham Saif Emon (PLoS ONE, 2025)
Upstream Contamination is a counter-intuitive phenomena of fluid dynamics, where particles can go against the liquid stream and climb, higher containers. Previous studies have attributed the movement of particles against the flow of water to the Marangoni effect, where surface tension gradients drive fluid movement. However, the effect was not enough to account for the motion of particles. Meanwhile, this study challenges that explanation by documenting the ascent of fine particles of Iron Fillings, through a water jet where the lower container exhibited higher surface tension due to an aqueous calcium chloride (CaCl2) solution. Contrary to the Marangoni effect, which predicts that particles should move from areas of lower to higher surface tension, our observations showed that the particles can move upwards even from a higher surface tension to a lower surface tension region. Afterward, other factors influencing this phenomenon were studied, including the height of the upper container from the lower one, the angle between the channel and the horizontal axis, temperature, and surface tension gradient. Each of them, suggests that factors other than surface tension gradients, such as fluid dynamics and turbulence, play a significant role in particle behavior in these conditions. This study can help us understand how some ‘safe-ecosystems’, cell mechanisms and medicine production can be contaminated in an unthinkable way so that these contaminators can be prevented and a safer ecosystem and medicare development can be ensured and steps to safeguard protoplasm from harmful contaminants can be taken.